- #1

- 2

- 0

m = - q/p

1/f = 1/p + 1/q

I just need to show that they are equal, but im getting confused with the maths..

q= (1 - (q/p)) (1/(1/p + 1/q))

q= (1 - (q/p))(qp/(p+q)

q= (qp/p + q) - (q/p)(qp/(p+ q)

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter ben488
- Start date

- #1

- 2

- 0

m = - q/p

1/f = 1/p + 1/q

I just need to show that they are equal, but im getting confused with the maths..

q= (1 - (q/p)) (1/(1/p + 1/q))

q= (1 - (q/p))(qp/(p+q)

q= (qp/p + q) - (q/p)(qp/(p+ q)

- #2

Chi Meson

Science Advisor

Homework Helper

- 1,789

- 10

- #3

Doc Al

Mentor

- 45,093

- 1,397

Good. Rearranging, this becomes:I just need to show that they are equal, but im getting confused with the maths..

q= (1 - (q/p)) (1/(1/p + 1/q))

q= (1 - (q/p))(qp/(p+q)

q= [(p-q)/p][qp/(p+q)] = [(p-q)/(p+q)]q

Well, looks like it's

Perhaps they meant to write: q = (1-m)f

- #4

Chi Meson

Science Advisor

Homework Helper

- 1,789

- 10

q= (1+m)f

is derived directly from the thin-lens and magnification equations, if you use m=q/p (no negative).

So the equation q=(1+m)f is a general equation (true for all real situations) not a specific equation, as long as you are using the non-negative convention for the magnification equation.

There is a problem with the question, as stated.

- #5

- 2

- 0

thanks so much for all your help, its great.

Ben

Ben

Share: